Anatomical Adaptations of Halophyte Leaves (Nitraria retusa [Forsskal] Asch. and Atriplex halimus L.) in Response to Cement Dust Pollution in Arid Environments - Nouha Krir; Mounira Mkaddem Guedri; Mehrez Romdhane; Manel Abdullah Alshaqha (Life)
This study investigates the anatomical adaptations of leaves from two halophyte species, Nitraria retusa (Forsskal) Asch. and Atriplex halimus L., in response to pollutants from a cement factory and human activities. In industrial areas, these plants absorb pollutants through their leaf surfaces, including Cu, Zn, and Pb. The two species were examined for anatomical changes under air pollution, and key factors including leaf blade thickness, palisade parenchyma cell height, spongy parenchyma cell diameter, epidermal characteristics, and stomatal traits were assessed. Under pollution, the leaves displayed smaller and denser stomata and idioblasts in the palisade and spongy parenchyma. These anatomical responses suggest that N. retusa and A. halimus could be effective bioindicators for detecting cement dust pollutants. Their leaf relative water content (RWC) exhibited a range of values: 70.1% and 87% for N. retusa and 64.8% to 74.2% for A. halimus on the highly polluted site (S1) and the control site (S4), respectively. Notably, a statistically significant site effect was observed (p > 0.01), confirming previous studies, and indicating reduced leaf relative water content (RWC) values in plants exposed to heavy metals like Cd and Pb. Heavy metals can lead to mineralization by binding to cell walls, altering their physicochemical properties and plasticity. Furthermore, significant correlations between specific heavy metals and histological parameters in A. halimus leaves indicated potential interactions between metal composition and leaf structure, highlighting their role in modulating anatomical adaptations. The correlation of leaf thickness, upper epidermal thickness, and stomatal density with Zn and Pb levels underlines the importance of these anatomical features in heavy metal accumulation and retention in plant tissues.